IMPLEMENTASI SISTEM PENDAFTARAN ONLINE SD MUHAMMADIYAH BANYUWANGI KABUPATEN PRINGSEWU BERBASIS WEB MOBILE - Septiawan, Andri; Tri Handayani, Lilis (YHMM PUBLISHING, 2023)
SD Muhammadiyah Banyuwangi is a school located in Pringsewu Regency, Lampung. Currently, the admission of new students still uses a manual system so that people who are far from the school sometimes have difficulty registering their children at this school. This problem is what made researchers conduct research and design an online registration application at SD Muhammadiyah Banyuwangi. The purpose of this study is to create a web-based mobile online registration application and provide convenience to school employees in making new student admission reports. The usefulness of this application system is to make it easier for new students to register at SD Muhammadiyah Banyuwangi and make it easier to store new student data. With this application system, new student registration can be done online using a smartphone connected to the internet network so that registration can be done anywhere.